Morality and Ethics in Education and its Impact on the Society - Hoque, Muhammad Aminul (IIUC Studies, 2015)
The technology has been developing tremendously in the modern world with remarkable contribution in various sectors of human life, but it has failed to address the most important issues of morality and ethics. The lack of which has resulted the killing, eve teasing, degeneration and life of human beings has become cheaper than anything else. This is why, the need for a study on the importance of Islamic Values has become essential to arrest the degeneration and lawlessness in the society and make the people aware about their duties and responsibilities afresh. This research Article is highly expected to address this problem. IIUC Studies Vol.9 December 2012: 335-344